Factors Affecting the Age of Admission of Postmenopausal Women to an Osteoporosis Outpatient Clinic - Ferda Özdemir,; Şenay Demir Yazıcı,; Derya Demirbağ Kabayel,; Necdet Süt, (Archives of Rheumatology, 2010)
Objective: In the present study, the factors that may potentially affect the age of admission of postmenopausal women to an osteoporosis (OP) outpatient clinic were evaluated. Materials and Methods: Two hundred and twenty-six postmenopausal women admitted to our OP outpatient clinic were studied retrospectively. The level of education, occupation, age at menopause, duration of menopause, history of hormone replacement therapy (HRT), exercise routine, history of medication use that may cause secondary OP, and family history of OP were questioned. Lumbar spine and femur bone mineral density (BMD) measurements were performed by dual energy x-ray absorptiometry (DEXA). The data were analyzed by linear regression. Results: The mean age of the patients was 58.8±8.7 years (range, 37-82 years) and the mean age at menopause was 45.2±5.8 years. Multiple backward stepwise linear regression was performed. When factors which could potentially affect the age of admission to OP outpatient clinic were included in the model, only 2 factors (age at menopause and duration of menopause) were shown to affect the age of admission. These two variables explained 98.9% of the variation (adjusted R2) in admission age (p < 0.001). Conclusion: The most important factors affecting the age of admission of postmenopausal women to the OP outpatient clinic were determined to be the age at menopause and the duration of menopause. (Turk J Rheumatol 2010; 25: 72-6)